Abnormally high expression of CHI3L1 in peripheral blood mononuclear cells and serum and their potential diagnosis and prediction from lymphoma patients - Wang, Chao; Tang, Langui; Luo, Haibing; Liang, Juan; Huang, Yanzhao; Guo, Kaiyun; Liu, Rong; He, Yuxing; Gao, Yan; Lei, Ming (Frontiers in Immunology, 2025)
AimThis study aimed to investigate the expression of CHI3L1 in aggressive lymphomas and assess its potential as a diagnostic and prognostic biomarker.MethodologyThis study investigates the expression of CHI3L1 protein in the peripheral blood of patients with aggressive lymphoma and healthy controls using enzyme-linked immunosorbent assay (ELISA). The prognostic significance of CHI3L1 was assessed through Cox regression and Kaplan-Meier survival analyses. The differences in CHI3L1 expression between lymphoma and control samples were analyzed using the lymphoma-related gene expression datasets GSE25638 and GSE56315, as well as their combined dataset (GSE25638 and GSE56315). Subsequently, a prognostic analysis of CHI3L1 was conducted using the lymphoma tissue sample gene expression dataset GSE31312. Weighted gene co-expression network analysis (WGCNA) identified genes co-expressed with CHI3L1, and a protein-protein interaction (PPI) network was constructed. RT-qPCR was used to further validate CHI3L1 expression in peripheral blood mononuclear cells (PBMCs) from lymphoma patientsResultsThe serum CHI3L1 protein expression in patients with aggressive lymphoma was significantly higher than that in healthy controls (p<0.001). Moreover, CHI3L1 levels were significantly elevated in stage III~IV patients compared to stage I~II patients (P = 0.001). One-way Cox regression and Kaplan-Meier analyses further demonstrated that high CHI3L1 expression was closely associated with shorter overall survival (p<0.001). Bioinformatics analysis revealed that CHI3L1 expression was significantly elevated in lymphoma samples compared to normal controls (p < 0.05), with diagnostic AUC values of 0.92, 0.99, and 0.93, indicating high diagnostic accuracy. Furthermore, patients with high CHI3L1 expression exhibited significantly shorter overall survival (p < 0.05), suggesting a potential association with poor prognosis. Co-expression analysis identified 605 genes associated with key biological processes, including the inflammatory response, signal transduction, and apoptosis. These genes were enriched in functional pathways such as mineral uptake and the Toll-like receptor signaling pathway. Validation experiments confirmed that CHI3L1 gene expression in PBMCs of patients with aggressive lymphoma was significantly higher than that in healthy individuals (p<0.01).ConclusionThis study demonstrates that elevated CHI3L1 expression is strongly associated with lymphoma onset, progression, severity, and poor prognosis, underscoring its potential as both a diagnostic and prognostic biomarker. Moreover, CHI3L1 may contribute to lymphoma progression by regulating key biological processes.